Lithium cation as radical-polymerization catalyst - Clark, Timothy (Journal of the American Chemical Society, 2006)
Density-functional theory (DFT) and ab initio (QCISD and CBS-RAD) calculations suggest that complexation of "naked" lithium cations to olefins favors the addition of alkyl radicals to the double bond over abstraction of an allyllic hydrogen atom. Thus, "naked" lithium cations in nonpolar solvents can catalyze the radical polymerization of olefins by favoring the chain-lengthening reaction over the competing hydrogenatom extraction, which is competitive in the absence of metal ions. One putative initiation reaction, addition of triplet dioxygen to the double bond, is thermoneutral and has a very low barrier when the oxygen molecule is complexed to a lithium cation. An alternative process, abstraction of an allyllic hydrogen atom to generate the allyl and hydroperoxy radicals, is also strongly favored by complexation of the oxygen to the lithium cation but is less favorable than addition. These results support Michl's recent interpretation of experimentally observed alkene polymerization in the presence of lithium salts of hydrophobic carborane anions.
Keywords: \